Clinical practice 3D-printed wound chambers: a novel splint system for wound healing research. Issue 2 (19th May 2021) - Tang, Jordan; Halaseh, Faris; Khan, Nawal; Zaki, Daniel; Ziegler, Mary; Sayadi, Lohrasb; Evans, Gregory; Widgerow, Alan D.
No abstract available